International Financial Reporting Standards Convergence and Quality of Accounting Information: Evidence from Indonesia - Yusrina, Hasyyati; Mukhtaruddin, Mukhtaruddin; Fuadah, Luk Luk; Sulong, Zunaidah (International Journal of Economics and Financial Issues, 2017)
The International Financial Reporting Standards (IFRS) initiated by International Accounting Standard Board (IASB) are principle-based standard that require extensive disclosure of financial statements and accounting information as compared to prior standard that is the Generally Accepted Accounting Principles (GAAP) to better reflect the overall quality of company’s performance. Therefore, the IFRS convergence is expected to improve the reliability of financial reporting by limiting opportunistic managerial discretion. The conjecture is the mandatory adoption of IFRS will reduce the managerial discretionary behaviors to engage in earnings management practices, thus improving earnings quality and value relevance of accounting quality information. High quality of accounting information in terms of earnings quality and value relevance can stimulate investors’ behavior in the stock market exchange. This study utilises a sample of 110 manufacturing sector companies for the years 2009 to 2014, to include pre-IFRS (2009 to 2011) and post-IFRS period (2012 to 2014). The data is analyzed using multiple regression technique by using the pooled least square method. The results of earnings management model of the study indicate that there are significantly positive relationship between size and leverage on earnings management. Whereas, the level of gross fixed assets is found to have a significant negative effect on earnings management. While, value relevance model the result shows there are significantly positive relationship between earnings per share (EPS), book value per share (BVPS) and size. Whereas, the leverage is shows significantly negative effect to earnings management. Overall, this study provides evidence of effect of IFRS convergence on the quality of accounting information is increase in term of value relevance but decrease in term of earning management. Keywords: IFRS Adoption, Earning Quality, Earning per Share, Book Value per Share JEL Classifications: M41, G11